Proporsi Spermatozoa Y Hasil Pemisahan Dengan Fraksi Albumen Telur dan Lama Penyimpanan Semen Domba Lokal - Akhdiat, Tedi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
This research was conducted  to determine the  quality and proportion of Y-spermatozoa with more fraction of egg white and storage period. The experimental method with completely Randomized Design base on Factorial consist  of two factor were used. The first factor was F  (egg white) consist of level f1 = 5  and 25 %;  f2 = 10  and 30 %; f3 = 15  and 35 %; and second factor is L (strorage period) consist of level l0 = 0 hours; l2 = 2 hours; l4 = 4 hours. Each treatment was replicated four times. The variable measured were  motility(%), live spermatozoa (%), abnormality (%), and proportion of Y-spermatozoa.  The results showed that fraction and storage period had no significant interaction       (P > 0.05) on the all variable. The   effect fraction of  egg white showed no significant (P > 0.05) difference on percentages motility, live spermatozoa, and abnormality. However the fraction showed significant (P < 0.05) on difference   proportion of Y-spermatozoa. The effect of storage period showed highly significant (P < 0.01) difference on motility and significant (P < 0.05) difference on  live spermatozoa. However, the storage periode showed no significant (P > 0.05) difference on abnormality, and proportion of Y-spermatozoa. Kept of spermatozoa for four hours product mean of motility 61.67 percent, live spermatozoa 63.25 percent, consentration were 932.54 ± 76.34 million spermatozoa/ml of semen, while albumen fraction of f2 (10  and 30 %) gave the highest result in motility and live spermatozoa : 71.67 and 74.79 %, respectively.